Quality of life among infertile women with endometriosis undergoing IVF treatment and their pregnancy outcomes - Meng-Hsing Wu; Pei-Fang Su; Wei-Ying Chu; Chih-Wei Lin; New Geok Huey; Chung-Ying Lin; Huang-Tz Ou (Taylor & Francis Group, 2021)
Objective We assessed the quality of life (QoL) and pregnancy outcomes of in vitro fertilization (IVF) treatment among infertile women with endometriosis, as compared to infertile women without endometriosis. Study design Eighty-one (81) endometriosis women (with 142 embryo transfer [ET] cycles) and 605 non-endometriosis women (with 1063 ET cycles) were included. QoL was measured by FertiQoL at the date before ET. Pregnancy outcomes included biochemical pregnancy, ongoing pregnancy and live birth. Generalized estimating equation analyses were performed to assess the association between QoL and IVF pregnancy. Results Endometriosis-affected women had significantly lower QoL, as indicated by mind/body, treatment environment and total treatment scores, and total scores of FertiQoL (p < .05), compared to those without endometriosis. Among non-endometriosis women, QoL scores were significantly associated with successful IVF pregnancy; with one unit increase in QoL scores as measured by emotional domain of FertiQoL, the probabilities of ongoing pregnancy and live birth significantly increased by 2.5% and 2.8%, respectively (p < .05). This association was also observed among endometriosis women but it did not reach statistical significance. Conclusions Lower QoL among women with endometriosis versus non-endometriosis during IVF treatment highlights the importance of developing strategies to improve their QoL, which may enhance following pregnancy rates in this population.